Raman spectroscopy investigation of inter-diffusion in GaP/Ge(111) heterostructures. (January 2019) - Aggarwal, R.; Ingale, Alka A.; Dixit, V.K.; Sathe, V.
Abstract: GaP/Ge(111) heterostructures are investigated for the observed red-shift and increased full width at half maximum of Ge optical phonon using Raman spectroscopy. Results are discussed in the light of inter diffusion of substrate and layer elements at the hetero-interface. Wavelength dependent Raman spectra show the co-existence of inter diffused layer (∼20 nm) below the GaP nucleating layer that is grown at 425 °C with high V/III ratio (∼1725). However, GaP/Ge(111) thick layer grown at 770 °C having same nucleating layer does not show presence of an inter diffused layer. Consistently, nucleating layer thermally treated at 700 °C, close to thick layer growth temperature, does not show the presence of such an inter diffused layer. The study paves the way for probing an inter diffused hetero-interface without damaging the sample using Raman spectroscopy. Further, these results are very useful for understanding the role of nucleating layer for the integration of III-V on germanium. Highlights: Inter diffusion at GaP/Ge interface is investigated using Raman spectroscopy. Wavelength dependent Raman confirms disordered Ge layer (∼20 nm) near heterointerface. Thermal treatment of nucleating layer improves crystalline quality of heterointerface. The results can be used for solving the challenges in growth of polar on non-polar.